2019
DOI: 10.1002/malq.201900045
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafilter extensions do not preserve elementary equivalence

Abstract: We show that there exist models M1 and M2 such that M1 elementarily embeds into M2 but their ultrafilter extensions β β(M1) and β β(M2) are not elementarily equivalent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Ultrafilter extensions of arbitrary n-ary maps (and, more broadly, of first-order models) have been introduced independently in recent works by Goranko [2] and Saveliev [3,14]. Further studies can be found in [15,16,17,18].…”
Section: Application To the Theory Of Ultrafiltersmentioning
confidence: 99%
“…Ultrafilter extensions of arbitrary n-ary maps (and, more broadly, of first-order models) have been introduced independently in recent works by Goranko [2] and Saveliev [3,14]. Further studies can be found in [15,16,17,18].…”
Section: Application To the Theory Of Ultrafiltersmentioning
confidence: 99%
“…Both theorems remain true for isomorphic embeddings and some other modeltheoretic interrelations (see [15,27,28]). On the other hand, it is shown in [32] that Theorem 1.7 does not hold for elementary embeddings, moreover, the ultrafilter extensions of a model and its elementary submodel do not need to be elementarily equivalent.…”
Section: Ultrafilter Extensions Of Modelsmentioning
confidence: 99%
“…Another notation was used in[15], where A * was denoted by U(A), and in[27,28,32], where A was denoted by β A.…”
mentioning
confidence: 99%
“…Moreover, both theorems remain true for isomorphic embeddings and some other modeltheoretic interrelations (see [1,3,4]). It was shown in [28] that Theorem 2 does not hold for elementary embeddings, moreover, the ultrafilter extensions of a model and an its elementary submodel can be even non-elementarily equivalent.…”
Section: Introductionmentioning
confidence: 99%
“…Another notation was used in[1] where A˚was denoted by UpAq and in[3,4,28] where Ă A was denoted by β β A.…”
mentioning
confidence: 99%